2019
DOI: 10.1016/j.actpsy.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Lost in the forest? Global to local interference depends on children's reading skills

Abstract: We studied the global precedence effect in primary school children with and without developmental dyslexia, using a compound figures task with familiar (Latin) or unfamiliar (Hebrew) letters. The two components of the global precedence effect were considered separately: global advantage (faster processing of global than local letters) and asymmetric interference (global distracters interfere with local targets but not vice versa). Both groups of children showed a global advantage with familiar as well as with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Together these results suggest that dyslexia may be associated with impaired RH processing in flexibly switching between holistic and part-based representations. This speculation is consistent with recent research suggesting that children with dyslexia may have deficits in coordination between analytic and holistic processing needed for fluent reading (e.g., Lachmann, 2018;Schmitt, Lachmann, & Leeuwen, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Together these results suggest that dyslexia may be associated with impaired RH processing in flexibly switching between holistic and part-based representations. This speculation is consistent with recent research suggesting that children with dyslexia may have deficits in coordination between analytic and holistic processing needed for fluent reading (e.g., Lachmann, 2018;Schmitt, Lachmann, & Leeuwen, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, we think that letter and sex differences according to hormonal status are modulating variables that are relevant to the GPE and should be taken into account in any study on global/local processing, including research on neural correlates in visual processing of hierarchical stimuli (of interest, are event related potential studies such as those carried out by Flevaris et al, 2014 andIglesias-Fuster et al, 2015 and the fMRI study carried out by Valdés-Sosa et al, 2020). We also maintain the view that the variables letter and sex according to hormonal status should be taken into account in studies analysing global/local processing in relation to face processing (Behrmann et al, 2005;Bentin et al, 2007;Duchaine et al, 2007a,b;Busigny and Rossion, 2011), reading skills and developmental dyslexia (Schmitt et al, 2019) as well as in other studies on the GPE at different stages of the life cycle, specifically during typical ageing (Lux et al, 2008;Agnew et al, 2016) and in neurodegenerative disorders (e.g., Alzheimer's disease, Slavin et al, 2002;Pike, 2017), in this case for the purpose of characterising cognitive degeneration markers allowing early detection and neurocognitive intervention. AG and EO: methodology.…”
Section: Letter and Sex Are Variables To Be Taken Into Account In Stumentioning
confidence: 98%
“…For example, Lachmann et al (2014) showed that the GPE disappears for letters if the visual angle mimics conditions of reading of individual letters, while it remains for non-letters. However, later, Schmitt et al (2019) found that this design effect depends on children's reading skills. With regard to the subjective variable of interest here (i.e., sex), earlier studies applying the Navon task found smaller RTs in men than in women, both in directed (Martin, 1979b) and in divided (Lee et al, 2012) attention tasks, the latter requiring simultaneously global and local attention.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that a decreased weighting or reliance on global information in dyslexic readers could be due to a dorsal stream deficit, as the dorsal stream is specialized for low spatial frequency/global processing. Similarly, Schmitt et al 122 report that dyslexic children, unlike controls, show no global-to-local interference in the Navon task which the authors interpret as an overreliance on analytic processing as opposed to holistic or global processing. Conversely, compared to typical readers, dyslexic readers showed signs of stronger holistic processing of English words 71 and Chinese characters 106 , 123 , and illiterates process both faces and houses more holistically compared to controls 124 .…”
Section: Discussionmentioning
confidence: 95%